Pharmacovigilance in ophthalmology in Switzerland: an analysis of the most frequently reported ocular adverse drug reactions within the last 25 years (Swiss Medical Weekly, 2019)
AIMS OF THE STUDY Although systemic drugs can exert local effects on the eye, ophthalmology is a medical specialty with perhaps the fewest assessed adverse drug reactions (ADRs), representing a particular challenge in pharmacovigilance. Our aim was to quantify ADRs in ophthalmology in Switzerland, with a focus on angiogenesis inhibitors. METHODS Individual case safety reports (ICSRs) on suspected ADRs reported in Switzerland from January 1991 to June 2016 were extracted from the WHO Global ICSR database, VigiBase™. ICSRs were analysed in relation to treatment duration, patient age, route of administration, patient sex and reported symptoms. RESULTS A total of 80,515 ICSRs were reported in Switzerland during the reference period. Reactions linked to eye disorders accounted for 2793 (3.5%) cases. The main Anatomic Therapeutic Chemical / Defined Daily Dose drug classes associated with eye disorders were drugs acting on the nervous system (27.7%) followed by drugs “acting on sensory organs” (20.2%) and antineoplastic agents (18.0%). Most cases involved adult patients (70.6%). Patients over 60 years accounted for 815 (29.2%) ICSRs, and reactions in children were significantly less frequent (8.2%). Older patients were exposed to a higher number of drugs, and the majority of serious reactions involved children and older patients. A significant positive correlation between polypharmacy and seriousness of reported reactions was observed. The reported drugs were categorised as “suspected” in 51.1%, “concomitant” in 43.3% and “interacting” in 2.6% of cases. “Visual impairment” was the most commonly reported adverse reaction, experienced by 635 (22.7%) of patients (7.2% of all reported eye-related symptoms). The majority of reactions were transient, as 4173 (47.1%) completely resolved. Severe reactions included fatal outcome in 18 patients (0.6%) and blindness in 78 patients (2.6%). Since 2000, the intravitreous vascular endothelial growth factor (VEGF) inhibitors bevacizumab, aflibercept and ranibizumab accounted for 99 ICSRs. Retinal haemorrhage (reporting odds ratio [ROR] 10.36, 95% confidence interval [95% CI] 2.65–40.50; p